The Influence Of Determinant Factors On Consumer Satisfaction That Mediates Repurchase Intention In Online Shopping Of Multivitamin Supplements During The Covid-19 Pandemic In Indonesia - Cory Primaturia; Margaretha Pink Berlianto (Institute of Computer Science (IOCS), 2022)
The online purchase of multivitamins during the COVID-19 pandemic has increased significantly because of not only the fact that until now there is no specific treatment for the infection but also the fear of being infected. This study aims to investigate the direct influence of determinant factors of customer satisfaction, and the mediating factors of customer satisfaction and fear of COVID-19 in increasing repurchase intentions during the pandemic on multivitamin and micronutrient. This study used quantitative research and data collection was collected using questionnaire. The target population of this research were people that have purchased online multivitamin in e- commerce in Indonesia during pandemic COVID-19. The number of samples were determined to be which 254 samples. The sampling technique use was purposive sampling. Partial Least Square-Structural Equation modelling (PLS-SEM) is applied to this study. The study result indicated that the repurchase intention was positively affected by customer satisfaction that effected by site design, product price, time saving, product information linked to customer satisfaction and directly influenced by the fear of COVID-19. Practical implication of this study suggests that to retain repurchase intention during this pandemic, practitioner of m-commerce should increase their customer satisfaction by improving the determinant factors of e-commerce and taking emotional factor into consideration.